Microwave generation by supercritical REB at plasma assistance - Chupikov, P.T.; Onishchenko, I.N.; Prokopenko, Yu.V.; Pushkarev, S.S.; Yegorov, A.M. (Вопросы атомной науки и техники, 2004)
The experimental researches on generation of microwave radiation in a system with a supercritical current of a
relativistic electron beam produced in the magnetically isolated diode and external plasma source are carried out.
The researches have shown that in the presence of external plasma the power of microwave radiation is increased in
comparison to vacuum system. Проведені експериментальні дослідження генерації НВЧ випромінювання в системі з надкритичним
струмом релятивістського електронного пучка і зовнішнім плазмовим джерелом. Дослідження показали, що
при наявності зовнішньої плазми потужність НВЧ випромінювання збільшується в порівняні з вакуумною
системою. Проведены экспериментальные исследования генерации СВЧ излучения в системе со сверхкритическим
током релятивистского электронного пучка и внешним плазменным источником. Исследования показали,
что при наличии внешней плазмы мощность СВЧ излучения увеличивается по сравнению с вакуумной системой.